2018
DOI: 10.1093/inthealth/ihx075
|View full text |Cite
|
Sign up to set email alerts
|

Association of job sectors with type 2 diabetes mellitus, hypercholesterolemia and obesity: a cross-sectional study from the Malaysian Cohort (TMC) project

Abstract: BackgroundThe investigation of risk factors of cardiovascular disease (e.g., major endocrine, nutritional and metabolic diseases) across job sectors is useful for targeted public health intervention. This study examined the occurrence of type 2 diabetes mellitus (T2DM), hypercholesterolemia and obesity in 21 job sectors in the general population.MethodsA baseline cross-sectional analysis of the Malaysian Cohort was conducted, which included 105 391 adults. Multiple logistic regression analyses were conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
1
8
0
3
Order By: Relevance
“…Ao verificar a média de horas de sono, constatou-se que não houve associação significativa, embora exista variação nas horas de sono dos dias de folga para os dias de trabalho. Ademais, estudos revelam que ter problemas relacionados ao sono ou trabalhar em períodos noturnos são fatores de risco para DM (11,28) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Ao verificar a média de horas de sono, constatou-se que não houve associação significativa, embora exista variação nas horas de sono dos dias de folga para os dias de trabalho. Ademais, estudos revelam que ter problemas relacionados ao sono ou trabalhar em períodos noturnos são fatores de risco para DM (11,28) .…”
Section: Resultsunclassified
“…Autores apontam que a obesidade possui relação importante com o quadro de DM. O aumento de peso, juntamente com o acúmulo de tecido adiposo na região abdominal, resulta em inúmeras alterações fisiológicas que podem impactar de forma negativa na saúde dos trabalhadores (11,12) . O presente estudo é justificado pela necessidade em estimar os fatores associados às alterações glicêmicas no trabalhador feirante, visto que a transição epidemiológica trouxe mudanças nos padrões de saúde/doença, resultando no aumento das doenças crônicas, dentre elas, a DM.…”
unclassified
“…23 The consequent benefits on mental health influence quality of life with direct consequences to the lifestyle-related chronic health diseases. A powerful cross-sectional study by Borhanuddin et al, 2018 24 researched among 105,391 Malaysian adults in 20 job sectors consolidated this assertion. The nationwide study found T2DM prevalence was highest accommodation and food service activities with unemployed/ homemaker emerged as the single job sector with the highest prevalence of hypercholesterolaemia.…”
Section: Associated Factors Of T2dm Among Adult Respondentsmentioning
confidence: 97%
“…The nationwide study found T2DM prevalence was highest accommodation and food service activities with unemployed/ homemaker emerged as the single job sector with the highest prevalence of hypercholesterolaemia. 24 Employment illuminates the biopsychosocial framework of health determinants which explain the prevalent of T2DM in this community. Therefore, our findings suggest the holistic prevention strategies against T2DM need to depart from approach that transgress beyond just health and education, but also the economy.…”
Section: Associated Factors Of T2dm Among Adult Respondentsmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is an important cause of death globally with estimation of 17 million deaths peryear (Borhanuddin et al 2018). Coronary heart disease and stroke are the most common cause of CVD deaths compared to other forms of CVDs.…”
Section: Introductionmentioning
confidence: 99%